Experimental and Numerical Investigation on Carbon Fiber-Reinforced Polymer-Strengthened Concrete Beam after High-Temperature Action of Asphalt Paving Construction - Xin Yuan; Chaoyu Zhu; Wei Zheng; Baijian Tang (Advances in Civil Engineering)
Numerical investigation of mechanical behavior of carbon fiber-reinforced polymer- (CFRP-) reinforced concrete beam after high-temperature action of asphalt paving construction was carried out in this study. The debonding failure of the CFRP plate-concrete interface was simulated by introducing the double debonding criterion. In order to compare with simulation results, specimens with different pavement schemes were tested to obtain experimental data. The load-deflection relationship, CFRP strain distribution, and crack propagation of specimens were compared with the numerical simulation results. The numerical simulation results showed good agreement with the experimental results. Additionally, the interface bonding stress distribution model and the calculation formula of the debonding bearing capacity were proposed. The proposed calculation model was proved to have good accuracy in predicting the strain of intermediate cracking debonding and the debonding bearing capacity of the CFRP-reinforced concrete beam after high-temperature action.